2017
DOI: 10.1556/168.2017.18.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Ground-level predation on artificial caterpillars indicates no enemy-free time for lepidopteran larvae

Abstract: Lepidoptera is one of the most diverse orders of insects, their larvae are very abundant in many habitats, and frequent prey of various predators. To decrease predation risk, caterpillars developed several means of defence, among them timing their activity to avoid predators (seeking enemy-free time). Although the enemy-free time hypothesis is often invoked to explain caterpillar behaviour, empirical evidence for it is scarce. We tested whether such enemy-free time exists in a temperate forest by comparing pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 52 publications
3
36
1
Order By: Relevance
“…Unlike the previous studies which divided diel time into only day and night (Seifert et al ., ; Ferrante et al ., ), our study subdivided diel time into four time intervals (morning, afternoon, early and late night). We found that both total predation rate and predation by ants were highest during the early night (19.00–01.00 hours).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike the previous studies which divided diel time into only day and night (Seifert et al ., ; Ferrante et al ., ), our study subdivided diel time into four time intervals (morning, afternoon, early and late night). We found that both total predation rate and predation by ants were highest during the early night (19.00–01.00 hours).…”
Section: Discussionmentioning
confidence: 99%
“…However, in a temperate forest, Ferrante et al . () found that predation rate at night was higher than during the day. Diel variability of predation pressure is still under debate, and potential drivers of such patterns are poorly understood.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations